Is home care an issue for primary health care? Expert views from Poland and Estonia - Põlluste, Kaja; Marcinowicz, Ludmiła; Chlabicz, Sławomir (Family Medicine & Primary Care Review, 2016)
Background . Home care (HC ) is placed between the health and social welfare systems, and the clients of HC mostly need health services. Along with other providers, family doctors (FDs) are usually involved in the provision of care. Objectives. This paper aims to describe and compare the involvement of HC providers to elderly and disabled persons in Poland and Estonia. Material and methods . This study is part of the international project EURHOMA P (Mapping Professional Home Care in Europe). Data was collected in 2008–2010. Experts from different areas of health and social care were queried by using a questionnaire containing structured case narratives, which were hypothetical descriptions of the situations of elderly or disabled persons living at home and in need of care. Results. There are a number of HC services, e.g. nursing, medical and social, available in both countries. The application for HC is mostly made by the patient or a close family member; the point of entry to HC can differ and depends on the client’s primary problem. FDs, together with social workers, play an important role in the provision of HC services in both countries. However, due to a shortage of round-the-clock professional services at a client’s home, families are also expected to play a large role in providing HC . Conclusions . Health care professionals, mainly those working in primary health care, play a remarkable role in access to and provision of HC services. Nevertheless, responsibility for 24-hour care lies, to a large extent, with the client’s immediate family. This situation seems to be typical in Eastern European countries.